Selection on the Drosophila seminal fluid protein Acp62F - Wong, Alex; Rundle, Howard (Université d'Ottawa | University of Ottawa, 2013)
Sperm competition and sexual conflict are thought to underlie the rapid evolution of reproductive proteins in many taxa. While comparative data are generally consistent with these hypotheses, few manipulative tests have been conducted and those that have provided contradictory results in some cases. Here, we use both comparative and experimental techniques to investigate the evolution of the Drosophila melanogaster seminal fluid protein Acp62F, a protease inhibitor for which extensive functional tests have yielded ambiguous results. Using between-species sequence comparisons, we show that Acp62F has been subject to recurrent positive selection. In addition, we experimentally evolved populations polymorphic for an Acp62F null allele over eight generations, manipulating the opportunities for natural and sexual selection. We found that the Acp62F null allele increased in frequency in the presence of natural selection, with no effect of sexual selection.
Keywords: Experimental evolution; natural selection; protease inhibitor; sexual selection; sperm competition.